2018
DOI: 10.1007/s13595-018-0733-7
|View full text |Cite
|
Sign up to set email alerts
|

How does economic research contribute to the management of forest ecosystem services?

Abstract: & Key message More and more environmental and resource economists are taking a particular interest in research on forest ecosystem services (FES), especially in a context of climate change. Spatial and temporal issues are crucial to economic analyses and for the design of conservation policies. Interdisciplinary research involving ecological and economic disciplines is a prerequisite for the more effective management of forest ecosystems. & Context Economists define non-market ecosystem services (ES) as public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…Waylen and Martin-Ortega (2018) suggested that future efforts should be done in reconsidering the balance between standardization and innovation, clarifying what fits within PES and what already exists in environmental management that can also be understood as PES schemes. It is always important when developing these schemes, keeping in mind, that the opportunity cost of providing ES should be covered by payments to constitute a true incentive and not the other way around (Garcia et al 2018).…”
Section: Types Of Payments For Ecosystem Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Waylen and Martin-Ortega (2018) suggested that future efforts should be done in reconsidering the balance between standardization and innovation, clarifying what fits within PES and what already exists in environmental management that can also be understood as PES schemes. It is always important when developing these schemes, keeping in mind, that the opportunity cost of providing ES should be covered by payments to constitute a true incentive and not the other way around (Garcia et al 2018).…”
Section: Types Of Payments For Ecosystem Servicesmentioning
confidence: 99%
“…The PES program benefits people directly, through direct payments and potentially new jobs, and indirectly, by promoting healthier ecosystems. Four concrete areas can be improved: (i) use simple indicators for environmental impact; (ii) target a specific social group; (iii) consider approaches to increase cost-effectiveness; (iv) define an impact evaluation tool for continuous monitoring National Program for Hydrological Environmental Services in Mexico (Alix- Garcia et al 2018;Porras et al 2013a) The main goal of the program is forest conservation or other vegetative cover in areas threatened by conversion or degradation. It offers annual payments per hectare over 5-year periods to private and communal landowners.…”
Section: Goalmentioning
confidence: 99%
See 1 more Smart Citation
“…PES are flexible, financial mechanisms for utilisation of available finances for environmental improvement. We can also characterise them as a reward for ensuring positive externalities (Daily, 1997) and their internalisation (Farley, Costanza, 2010;Garcia et al, 2018). Wunder (2015) described PES as voluntary transactions between service users and service providers that are conditional on agreed rules of natural resource management for generating offsite services.…”
Section: Characteristics Of Pes Schemesmentioning
confidence: 99%
“…the price is zero) and the forest owner will not consider the provision of this service in the same way as he or she would for a market good like timber. However, this non-market good or service has a value for the forest owner and for society (Garcia et al, 2018). Provisioning services are equivalents of forest production functions and include production of wood, game and other market products.…”
Section: Introductionmentioning
confidence: 99%